CONE BEAM COMPUTED TOMOGRAPHIC ANALYSIS OF ROOT AND ROOT CANAL MORPHOLOGY OF MANDIBULAR PREMOLARS IN A TERTIARY CARE CENTRE OF NEPAL - Kumar Chaudhary, Govind; Chaudhary, Sanjeeb; Gharti, Archana; Gupta, Abhishek; Ahmed, Sageer; Thapaliya, Bidhya; Singh, Harender (Journal of Chitwan Medical College, 2024)
Background: Mandibular premolars are challenging to treat endodontically due to their varied root and canal morphology, impacting treatment prognosis. This study aimed to assess the root and canal morphology of mandibular premolars in a Nepalese subpopulation using Cone Beam Computed Tomography (CBCT) images. Methods: A descriptive cross-sectional study was performed by obtaining 65 CBCT images of patients from the Department of Oral Medicine and Radiology of Chitwan Medical College, Chitwan, Nepal. A total of 130 untreated mandibular first and second premolars of both right and left side with completely developed roots were analyzed. The number of roots, root canals, their configurations per Vertucci’s classification, C-shaped canals, and the influence of gender and tooth position on morphology were evaluated. Results: Significant variations in root morphology were observed in mandibular premolars, with most having one root (85.4% in first premolars, 97.7% in second premolars) and one canal (78.5% in first premolars, 94.6% in second premolars). Type I configurations were most common (78.5% in first premolars, 94.6% in second premolars), followed by Type V (15.4% in first premolars, 2.3% in second premolars). C-shaped canals were more frequent in first premolars (20.8%) than second premolars (4.6%). Significant gender differences were noted in root and canal morphologies, with males showing more variability, but no significant differences were found based on tooth position. Conclusions: This CBCT study in a Nepalese subpopulation revealed significant root and canal morphology variations in mandibular premolars, emphasizing the importance of CBCT in endodontic diagnosis and treatment planning for better outcomes.